A case study on the application of the national building code provisions on light and ventilation in selected sleeping quarters of household help in condominium units in Metro Manila - Tolentino, Jun Gabriel Q. (College of Home Economics, University of the Philippines Diliman, 2019)
This research is a descriptive case study on the application of the National Building Code (NBC) provisions on light and ventilation in selected sleeping quarters of household help in condominium units in Metro Manila. The sleeping quarters of these domestic workers are often an overlooked area when designing residential spaces. A total of four (4) sleeping quarters of household help working in condominium units in Metro Manila, chosen through purposive sampling, were studied and analyzed through observation and interviews. The data collection was conducted in the span of two (2) weeks from the second week of April to the first week of May 2019. The findings show that almost all the sleeping areas were non-compliant to the NBC in terms of the size and dimensions, and airspace of the room. However, they were mostly compliant in terms of the ventilation, and size and placement of the window. Through the interview, it was discovered that the household help showed contentment towards the size and dimensions, and the airspace of the room. However, they mostly showed discontentment towards the ventilation, and the window openings. It was found that the compliance to the NBC provisions on light and ventilation was not always related to the perception of the household help. Several factors affected this outcome, which included personal background of the user, and environmental factors of the condominium. The researcher recommended a longer period of data collection, and further study on other factors such as privacy and personal space. The researcher also recommended further studies on other types of residential spaces such as houses.